Pengaruh Disiplin Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Kecamatan Ciputat Tangerang Selatan - Della Alviana Nursabela; Muger Apriyansyah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of work discipline and organizational culture on employee performance at the Ciputat District Office, South Tangerang City. The research employed a quantitative method with a total sample of 58 respondents using a saturated sampling technique. Data processing and analysis were conducted using SPSS version 29. The data analysis techniques included validity testing, reliability testing, classical assumption testing, simple and multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing.The results indicate that work discipline (X1) has a significant partial effect on employee performance (Y), as shown by the regression equation Y = 21.471 + 0.458X1. The correlation coefficient value of 0.551 indicates a moderate level of relationship, while the coefficient of determination of 0.304 or 30.4% suggests that employee performance is influenced by work discipline by 30.4%, with the remaining percentage influenced by other factors.Organizational culture (X2) also has a significant partial effect on employee performance, as indicated by the regression equation Y = 5.812 + 0.946X2. The correlation coefficient value of 0.815 reflects a strong relationship, with a coefficient of determination of 0.663 or 66.3%.Simultaneously, work discipline (X1) and organizational culture (X2) have a significant effect on employee performance, as evidenced by the regression equation Y = 4.827 + 0.084X1 + 0.876X2. The correlation coefficient of 0.670 indicates a strong relationship, with a contribution of 67% to employee performance.